2021
DOI: 10.3390/foods10071498
|View full text |Cite
|
Sign up to set email alerts
|

Sourdough Biotechnology Applied to Gluten-Free Baked Goods: Rescuing the Tradition

Abstract: Recent studies suggest that the beneficial properties provided by sourdough fermentation may be translated to the development of new GF products that could improve their technological and nutritional properties. The main objective of this manuscript is to review the current evidence regarding the elaboration of GF baked goods, and to present the latest knowledge about the so-called sourdough biotechnology. A bibliographic search of articles published in the last 12 years has been carried out. It is common to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 108 publications
(166 reference statements)
0
22
0
Order By: Relevance
“…It was previously reported that the glycemic index of GF bread is much higher compared to the traditional bread, exerting an influence over chronic diseases [ 47 , 48 , 49 ]. The strategies to reduce the glycemic response of starchy gluten-free products refers to the replacement of flours and starches with alternative raw materials (characterized by an increased content of dietary fiber, protein and resistant starch), the addition of viscous dietary fibers and application of different processing conditions such as grain germination, sourdough fermentation or hydration level [ 50 , 51 , 52 ].…”
Section: Hydrocolloids In Gf Breadmentioning
confidence: 99%
“…It was previously reported that the glycemic index of GF bread is much higher compared to the traditional bread, exerting an influence over chronic diseases [ 47 , 48 , 49 ]. The strategies to reduce the glycemic response of starchy gluten-free products refers to the replacement of flours and starches with alternative raw materials (characterized by an increased content of dietary fiber, protein and resistant starch), the addition of viscous dietary fibers and application of different processing conditions such as grain germination, sourdough fermentation or hydration level [ 50 , 51 , 52 ].…”
Section: Hydrocolloids In Gf Breadmentioning
confidence: 99%
“…Moreover, there is a trend to use fermentation processes in bread baking so that the products resemble sensory properties of sourdough bread, e.g., the use of sourdough made from gluten-free flour (e.g., [23]). In addition to organic acids, the lactic bacteria also produce free amino acids as precursors of flavours, contemporary degrade phytates and starch and change the fiber solubility.…”
Section: Raw Materials For Gluten-free Bread and Bakery Productsmentioning
confidence: 99%
“…The use of sourdough in gluten-free baked goods leads to products with improved technological and nutritional properties [23], which are softer, tend to stale more slowly and have a delayed mould spoilage rate and thus a prolonged shelf life. Sourdough also brings nutritional benefits because it makes minerals more available and its presence leads to the production of exopolysaccharides, which function as hydrocolloids [30].…”
Section: Microbial Fermentation In Gluten-free Bread Productionmentioning
confidence: 99%
“…Although being an ancient biotechnology, sourdough fermentation has gained renewed interest as a tool for better exploitation of non-wheat cereals in breadmaking [69]. Sourdough can be described as a mixture of flour and water fermented by lactic acid bacteria (LAB) or LAB in combination with yeasts, either spontaneous or inoculated [70].…”
Section: Sourdough Fermentationmentioning
confidence: 99%